The effect of advertising and sales promotion on television on brand awareness bukalapak on visitors to Padangsidimpuan City - Hardana, Ali; Replita, Replita; Damisa, Arti; Nasution, Jafar (Institute of Computer Science (IOCS), 2025)
Indonesia's market industry is the most competitive in Southeast Asia. This is evidenced by the large number of markets in Indonesia, which accept both foreign and domestic products. Market companies use various marketing strategies to increase public brand awareness. One of them is marketing through television media. Advertising content (X1) and sales promotion programs (X2) are offered and demonstrated as strategies to grow brand knowledge (Y) in the minds of potential customers. Bukalapak uses TV commercials to market. From 2021 to 2023, Bukalapak spent more money on advertising than all other online stores. The number of samples taken in this study amounted to 30 people, with the incidental sampling method. The sample size of 30 people was divided into two groups, each totaling 15 respondents, using a quasi-experiment. experiment. The first group was group who did remember the Bukalapak Harbolnas advertisement in December 2023. The results of this study indicate that the content of Bukalapak's advertisements can influence brand awareness of consumers by 75.4% can affect consumer brand awareness by 75.4%. This is based on with Bukalapak's totality in promotion through television which making Bukalapak as a marketplace brand with marketplace brand with the among others.